2016 International Conference on Selected Topics in Mobile &Amp; Wireless Networking (MoWNeT) 2016
DOI: 10.1109/mownet.2016.7496628
|View full text |Cite
|
Sign up to set email alerts
|

Contiki-AMAC — The enhanced adaptive radio duty cycling protocol: Proposal and analysis

Abstract: Energy-efficient operation is one of the prominent challenges for successful deployment of Wireless Sensor Networks (WSNs) along with maintaining certain quality of service (QoS) requirements. In this paper, we tackle the energy-efficient operation of WSN nodes implementation based on the Contiki real-time operating system (RTOS). We review the effect of applying spatial configuration for the radio duty-cycle (RDC) frequencies of WSN nodes running ContikiMAC. We propose an approach for enhancing the ContikiMAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…ESAFRP uses Adaptive MAC (AMAC) protocol which is derived from “CogNet” Cognitive Radio protocol architecture . Existing AMAC uses variable size packets from 500B (small packet) with 100mS time slot to 1500B (large packet) with 300mS time slots.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…ESAFRP uses Adaptive MAC (AMAC) protocol which is derived from “CogNet” Cognitive Radio protocol architecture . Existing AMAC uses variable size packets from 500B (small packet) with 100mS time slot to 1500B (large packet) with 300mS time slots.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…Energy efficiency is a mandatory requirement in the scope of Wireless Sensor Networks (WSNs), since these kind of networks are usually composed of battery-powered devices, whose batteries are not always easily replaceable [ 1 , 2 ]. For instance, one can mention either the lack of natural and economic resources or the harsh environments where many of such WSNs are placed as impairments for battery replacement [ 3 ]. Thus, it becomes of fundamental importance to spend efforts towards reducing the network energy consumption, extending its lifetime as much as possible [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that ContikiMAC provides better performance than X-MAC and its variants: lower latency and duty-cycle (i.e., lower energy consumption), and a higher packet delivery ratio (PDR) (i.e., fewer retransmissions). An enhanced adaptive radio D.C. version of Contiki (Contiki-AMAC) was proposed in [52]. [42] Variable, Synchronous Receiver-initiated Ultra-low Multi-hop TinyOS/Mica2 GES-MAC [56] Fixed, Synchronous Receiver-initiated Average Multi-hop Based on Mica2 RAPTS [57] Fixed, Synchronous Sender-initiated Ultra-low Multi-hop Propietary BailighPulse [58] Fixed, Synchronous Sender-initiated Ultra-low Multi-hop TinyOS/TelosB Guard beacon [59] Fixed, Synchronous Sender-initiated Low Multi-hop Contiki/T-mote sky L2 [60] Fixed, Synchronous Sender-initiated Low Multi-hop TinyOS/TelosB TAS-MAC [47] Variable, Synchronous Receiver-initiated Low Multi-hop TinyOS/TelosB RPL-BMARQ [48] Fixed, Synchronous Receiver-initiated Low Multi-hop Contiki/TelosB X-MAC [49] Fixed, Asynchronous Sender-initiated Low Multi-hop Contiki/Zolertia Z1 CONTIKI-MAC [50] Variable, Asynchronous Sender-initiated Very-Low Multi-hop Contiki/Zolertia Z1 AS-MAC [61] Fixed, Asynchronous Sender-initiated Low Multi-hop TinyOS/MicaZ& TelosB MCAS-MAC [54] Fixed, Asynchronous Sender-initiated Low Multi-hop TinyOS/Mica2 L-MAC [46] Variable, Asynchronous Receiver-initiated Very-Low Single-hop TinyOS/TelosB DuoMAC [53] Variable, Asynchronous Sender-initiated Low Multi-hop TinyOS/MicaZ a Duty-cycle: Average (10-25%), Low (1-10%), Very low (0.1-1%), Ultra-low (0.01-0.1%)…”
Section: Asynchronous DC Techniquesmentioning
confidence: 99%